Mercado de gás natural: o potencial brasileiro, seus entraves e condicionantes - CALFA, Anne Patryce Ferreira (2015)
Given the concern and global need for development with sustainability and increasing the Brazilian demand for natural gas, this study was premised on the assessment of the potential of the Brazilian natural gas market, analyzing its supply and demand trend, considering the influence of the regulatory issues, the pricing policy of its market, legal incentives and other conditions for its expansion. Public and private, national and international data were collected from official public documents and specific legislation, allowing a comparison of the national energy market with international and proposing actions that can widen the Brazilian natural gas supply and develop its market.